2017
DOI: 10.1186/s13287-017-0651-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering human ventricular heart muscles based on a highly efficient system for purification of human pluripotent stem cell-derived ventricular cardiomyocytes

Abstract: BackgroundMost infarctions occur in the left anterior descending coronary artery and cause myocardium damage of the left ventricle. Although current pluripotent stem cells (PSCs) and directed cardiac differentiation techniques are able to generate fetal-like human cardiomyocytes, isolation of pure ventricular cardiomyocytes has been challenging. For repairing ventricular damage, we aimed to establish a highly efficient purification system to obtain homogeneous ventricular cardiomyocytes and prepare engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…of the CMs increased about 40% to 1.6 μm, which is at the upper range of the sarcomere size in human fetal cardiac myocytes (1-1.7 μm). [25][26][27][28] Li et al 19 also showed an increase in sarcomere length when PSC-derived CMs were cultured over dECM, although their reported values (1-2.5 μm) were above the physiologic range for human CMs in vivo, suggesting overstretch of the cells in their studies.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…of the CMs increased about 40% to 1.6 μm, which is at the upper range of the sarcomere size in human fetal cardiac myocytes (1-1.7 μm). [25][26][27][28] Li et al 19 also showed an increase in sarcomere length when PSC-derived CMs were cultured over dECM, although their reported values (1-2.5 μm) were above the physiologic range for human CMs in vivo, suggesting overstretch of the cells in their studies.…”
Section: Discussionmentioning
confidence: 92%
“…This finding supports previous data showing electrical coupling of CMs that were cultured on the surface of dECM. 18,19 Because hESC-CMs typically have an immature phenotype in vitro, 20,21 some investigators have seeded these cells on dECM and other biomaterials to induce maturation. [22][23][24] We reasoned that incorporation of the cells into the matrix would be superior to surface coating because of the greater probability of matrix-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a stable transgenic hPSC line harboring fluorescent reporter under the transcriptional control of human myosin light chain-2V promoter (MLC2V) [130][131][132] and chick ovalbumin upstream promoter transcription factor II (COUP-TFII) [133] were developed to isolate ventricular and atrial cardiomyocytes, respectively. Despite the robust and high efficiency in enriching specific subtypes after cardiac differentiation of PSCs, the use of virus-based vector, again, has raised safety issues including immunogenicity and insertional mutagenesis risk that hinder their application in future clinical treatment.…”
Section: Diverse Cardiomyocyte Subtypes (Atrial Ventricular and Pacmentioning
confidence: 99%
“…First, a number of ventricular-specific reporter lines have been created to enrich the ventricular cardiomyocyte subtype (Table S1) [98]. In these reporter lines, a fluorescence protein is cloned into the endogenous MLC2v locus or driven by an MLC2v promoter for selection of ventricular-like cardiomyocytes [99,100]. This reporter can also be combined with a second cardiac marker such as NKX2.5 for double selection [101].…”
Section: Generation Of Atrial-like Cardiomyocytes From Human Pscsmentioning
confidence: 99%